PENINGKATAN KECERDASAN KINESTETIK MELALUI PERMAINAN GAMES BALL PADA ANAK USIA 4-5 TAHUN DI RA DAARUL MUTTAQIN BANTUR-MALANG - Ari Rohmania; Afifatu Rohmawati (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2024)
Games are one of the easy-to-apply learning techniques such as ball games. This game applies six techniques in early childhood kinesthetic learning. The purpose of this study was to describe the form and results of kinesthetic learning through ball games in children aged 4-5 years. The research methodology used is "Classroom Action Research" or classroom action research. Where, researchers will provide treatment in the learning process through several stages, namely the pre-cycle or experimental stage, cycle one, and cycle two by implementing three meetings in each cycle. Data collection techniques that will be used include observation, interviews, and documentation. By using mixmethod data analysis. The results of the study and discussion show that ball games use six techniques, including catching, throwing, bouncing, bouncing, kicking, and rolling. The technique is complex in improving children's kinesthetic abilities through the concept of outdoor learning. The learning methods used are competitive and cooperative. The results of data validation include a 61.8% increase in kinesthetics in the third meeting in cycle one with the technique of learning to kick through ball games. Meanwhile, the data of cycle two with a percentage of 89.7% of kinesthetic ability with rolling techniques through ball games. Thus, mastering learning devices is effective, creative and innovative. So that children are much more interested in following kinesthetic learning optimally.